2005
DOI: 10.1002/dmrr.600
|View full text |Cite
|
Sign up to set email alerts
|

Immunological mechanisms associated with long‐term remission of human type 1 diabetes

Abstract: Our observations support the concept that IL-10-dependent regulatory CD4(+) T-cell pathways are involved in beta cell recovery after the onset of hyperglycemia in autoimmune type 1 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Hence, it is suggested that these cells may predict good clinical outcomes by a specific regulatory response [39, 40]. Interestingly, a predominant IL-10 cytokine profile (and low IFN-γ secretion) in peripheral blood mononuclear cells was observed in 1 T1D patient with complete remission, with reported β-cell function [41]. Moreover, low serum IFN-γ concentrations at T1D clinical onset provide a strong positive predictive value for partial remission [42].…”
Section: Collateral Damage Of the T1d Remission Phase And Newly Propomentioning
confidence: 99%
“…Hence, it is suggested that these cells may predict good clinical outcomes by a specific regulatory response [39, 40]. Interestingly, a predominant IL-10 cytokine profile (and low IFN-γ secretion) in peripheral blood mononuclear cells was observed in 1 T1D patient with complete remission, with reported β-cell function [41]. Moreover, low serum IFN-γ concentrations at T1D clinical onset provide a strong positive predictive value for partial remission [42].…”
Section: Collateral Damage Of the T1d Remission Phase And Newly Propomentioning
confidence: 99%
“…This difference was not observed between children with diabetes recognized at a later age and age-matched healthy controls. The results of animal (Perez et al 2008;Cheatem et al 2009) as well as human studies (Karges et al 2006) highlight the role of cytokines IL-10 and TGF-b in the pathogenesis of T1D. Karges et al (2006) concluded that IL-10-dependent regulatory CD4 ?…”
Section: Discussionmentioning
confidence: 99%
“…The results of animal (Perez et al 2008;Cheatem et al 2009) as well as human studies (Karges et al 2006) highlight the role of cytokines IL-10 and TGF-b in the pathogenesis of T1D. Karges et al (2006) concluded that IL-10-dependent regulatory CD4 ? T cell pathways are involved in b-cell recovery after the onset of hyperglycemia in autoimmune T1D.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that there may be efficient regeneration of β-cells in children with T1D or having undergone subtotal pancreatectomy 5,67,68 . Also, insulin+/glucagon+ bihormonal cells have been described in human diabetic patients 6971 and upon ex vivo epigenetic manipulation 72 , suggesting that human α-cells might also display the plasticity allowing insulin production.…”
Section: Prospectivementioning
confidence: 99%